2020
DOI: 10.1007/s00261-020-02426-5
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography-guided radiofrequency ablation combined with transarterial embolization assisted by a three-dimensional visualization ablation planning system for hepatocellular carcinoma in challenging locations: a preliminary study

Abstract: Objective To assess the clinical efficacy and safety of computed tomography-guided radiofrequency ablation(CT-RFA) combined with transarterial embolization(TAE) assisted by a three-dimensional visualization ablation planning system(3DVAPS) for hepatocellular carcinoma(HCC) in challenging locations. Methods Data from 62 treatment-naive patients with hepatocellular carcinoma(HCC), with 83 lesions in challenging locations, and who met the Milan criteria and underwent CT-RFA between June 2013 and June 2016 were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The inquiry's techniques can increase the precision of impact after assessment next to the TACE therapy, limit the incidence of difficulties and adverse impacts, and so enhance the therapeutic impact of the sufferer with a liver tumor. In [16], the researchers assessed the medical safety and efficacy of CT-RFA, transarterial embolization, and a 3D visualisation ablation planning system (3DVAPS) in conjunction with computed tomography-guided radiofrequency ablation in difficult locations. For HCC in challenging regions, CT-RFA and TAE supplemented by a 3DVAPS provided excellent medical efficiency while being exceedingly safe.…”
Section: Related Workmentioning
confidence: 99%
“…The inquiry's techniques can increase the precision of impact after assessment next to the TACE therapy, limit the incidence of difficulties and adverse impacts, and so enhance the therapeutic impact of the sufferer with a liver tumor. In [16], the researchers assessed the medical safety and efficacy of CT-RFA, transarterial embolization, and a 3D visualisation ablation planning system (3DVAPS) in conjunction with computed tomography-guided radiofrequency ablation in difficult locations. For HCC in challenging regions, CT-RFA and TAE supplemented by a 3DVAPS provided excellent medical efficiency while being exceedingly safe.…”
Section: Related Workmentioning
confidence: 99%
“…The adoption of these techniques when performing the increasingly popular embolization/ablation combined procedures (commonly referred to as ‘double hit’ therapy), 22 , 23 , 24 , 25 in our experience, has resulted in decreased overall pain during and after the ablation segment of the procedure. Slow infusion of 50 ​mg lidocaine diluted into 50 ​cc of normal saline, administered in the target vascular bed over 2–4 ​min, mitigates the potential for pain during the initial infusion thought to be due to the acidic/low pH of lidocaine at room temperature.…”
Section: Techniquementioning
confidence: 96%
“…The use of intraarterial lidocaine before and after liver directed chemoembolization and embolization procedures has demonstrated safety and efficacy with respect to subjective pain both during and after therapy, resulting in a significant decrease in narcotic requirements when undergoing embolization. 22 , 23 , 24 , 25 Due to the innervation and arterial anatomy of the liver, the intraarterial administration of local anesthetic results in permeation into the subcapsular (and viscerally innervated) portion of the liver and exposure of anesthetic to the liver parenchyma, as well as the segmental portal triads and hepatic veins.…”
Section: Techniquementioning
confidence: 99%
“…However, no statistical differences were observed between the two groups in OS and RFS, which were affected by the comprehensive fact that larger tumors are more prone to developing satellites and vessels that feed the tumor ( An et al, 2020 ). In another study, RFA combined with TACE assisted by a 3D visualization ablation planning system provided optimal clinical efficiency for HCC in challenging locations and was verified as a highly safe treatment modality ( Huang et al, 2020 ). Although no statistically significant differences were detected in OS between the study group and the control group, however, the 1-, 2-, and 3-year LTP rates of the study group showed superior local control rates compared to the control group.…”
Section: Locoregional Therapiesmentioning
confidence: 99%